Characterization of a Suppressive Cis-acting Element in the Epstein–Barr Virus LMP1 Promoter - Yoshida, Masahiro; Murata, Takayuki; Ashio, Keiji; Narita, Yohei; Watanabe, Takahiro; Masud, H. M. Abdullah Al; Sato, Yoshitaka; Goshima, Fumi; Kimura, Hiroshi (Frontiers in Microbiology, 2017)
Latent membrane protein 1 (LMP1) is a major oncogene encoded by Epstein-Barr virus (EBV) and is essential for immortalization of B cells by the virus. Previous studies suggested that several transcription factors, such as PU.1, RBP-Jκ, NFκB, EBF1, AP-2 and STAT, are involved in LMP1 induction; however, the means by which the oncogene is negatively regulated remains unclear. Here, we introduced short mutations into the proximal LMP1 promoter that includes recognition sites for the E-box and Ikaros transcription factors in the context of EBV-bacterial artificial chromosome (BAC). Upon infection, the mutant exhibited increased LMP1 expression and EBV-mediated immortalization of B cells. However, single mutations of either the E-box or Ikaros sites had limited effects on LMP1 expression and transformation. Our results suggest that this region contains a suppressive cis-regulatory element, but other transcriptional repressors (apart from the E-box and Ikaros transcription factors) may remain to be discovered.